THE IMPACT OF THE LOCAL GOVERNMENT FINANCIAL INDEPENDENCE RATIO, THE LOCAL REVENUE EFFECTIVENESS RATIO, AND THE EXPENDITURE EFFICIENCY RATIO ON THE FINANCIAL PERFORMANCE OF REGENCIES AND CITIES IN ACEH PROVINCE - Marzuki; Nadia Mulya; Ghazali Syamni; Muttaqien (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study aims to analyze the impact of the local government financial autonomy ratio, the Local Own-Source Revenue (PAD) effectiveness ratio, and the expenditure efficiency ratio on the financial performance of regencies and cities in Aceh Province. This study uses a combination of cross-sectional and time-series data from 23 regencies and cities in Aceh Province for the years 2020–2024. The analysis method used is panel data regression using EViews 14. The results show that the local financial autonomy ratio and the PAD effectiveness ratio have a positive and significant effect on local financial performance. Meanwhile, the expenditure efficiency ratio does not have a significant effect on local financial performance. The combined effect of the local financial autonomy ratio, the PAD effectiveness ratio, and the expenditure efficiency ratio on local financial performance accounts for 92.36%, while the remaining 7.64% is influenced by other variables outside the scope of this study. The results of this study indicate that increasing local financial autonomy and the effectiveness of PAD management are key factors in improving local financial performance in the regencies and cities of Aceh Province.